Allergic manifestations in inborn errors of immunity: a systematic scoping review - Marbet, Lars; Gujer, Esther; Münger, Marlene H.; Killian, Michael P.; Mauracher, Andrea A.; Soomann, Maarja; Trück, Johannes; Pachlopnik Schmid, Jana (Frontiers in Immunology, 2025)
BackgroundAllergic diseases resulting from aberrant immune function are frequently observed in patients with inborn errors of immunity (IEI). However, the underlying monogenic disorders may not be initially diagnosed, which leads to delays in appropriate diagnosis and treatment. Although recent studies have highlighted the link between IEI and allergic conditions, earlier case series might not have been fully exploited.ObjectiveTo compile a comprehensive database of IEI cases in the literature, analyze the prevalence and characteristics of allergic diseases, and assess the latter’s association with other forms of immune dysregulation.MethodA systematic scoping review of the literature.ResultsA total of 738 articles (reporting on 3050 individual patients) were included. 226 (7.4%) of the patients were described as suffering from an allergy. Monogenetic diseases associated with a marked prevalence of allergy were found in various IEI subgroups. Food allergy was most frequently reported (n=172, 76.1%), followed by allergic rhinitis (n=56, 24.8%). The presence of allergy in patients with IEI was generally associated with the absence of other forms of immune dysregulation, although there were notable exceptions. The overall prevalence of atopic conditions (food allergy, allergic rhinitis, asthma, and eczema) in the dataset was 26.9% (n=821).ConclusionThis systematic scoping review emphasized the relevance of allergic diseases as a manifestation of immune dysregulation in IEI. Our findings might raise awareness of allergy in IEI among clinicians and researchers and constitute a valuable resource for better diagnosis and management of these conditions.